(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3dG jNai Cfg HfGA Ydi eG PcQfGg ef EecGf chf GdMce (B... (3eUH GdYehe GdQHGfj jbY GdJYGQV Hjf GWdGbg hGWdGb eJYdbg dcf HfGA Ydi eG PcQfGg ef EecGf GdJeSc HGdYehes
(3BNQgG (B:s
(3BNQgG(B: (3ajchf GdeSJUMH gh fLGSI Pdc GdPj cGf WGgkQG CYfj GdfLGSI GdMGOKI HGdedGbGI hfLGSI Pdc GdPj cGf fLkSG HYOe GdYde HGQJaGY GdfLGSJjf adGMX hJCeds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs